THE USE OF ART MANAGEMENT APPROACHES IN THE FORMATION OF A CREATIVE MANAGEMENT CULTURE IN HIGHER EDUCATION (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article investigates the role and significance of art management approaches in fostering a creative management culture within higher education institutions. The study substantiates the relevance of developing a creative management culture in the context of innovative development, digital transformation, and global competition in contemporary education systems. The research analyzes the potential of art management in promoting creative leadership, innovative thinking, organizational culture, and effective communication. The findings indicate that integrating art management approaches into higher education management contributes to improving educational quality and enhancing management effectiveness.